High consistency of trophic niches in generalist arthropod species (Oribatida, Acari) across soil depth and forest type - Lu, Jing‐Zhong; Cordes, Peter Hans; Maraun, Mark; Scheu, Stefan (Ecology and evolution, 2022)
Many traits including trophic niche parameters are attributed to species. However, generalist species may vary in trophic niches with environments, making species‐based knowledge hard to extrapolate beyond local food webs. Here we tested trophic consistency in oribatid mite species (Acari), one of the most abundant arthropods that occupy all trophic levels in soil food webs. We used stable isotope analysis to compare trophic niches of 40 Oribatida species that co‐occur in litter (OL) and soil (0–5 cm, mainly OF/H, AH) of five forest types (native European beech, non‐native Douglas fir, range‐expanding Norway spruce, two beech–conifer mixed forests). Although stable isotope signatures of bulk material differed between litter and soil, 13C and 15 N values of Oribatida species were remarkably stable irrespective of soil depth. Furthermore, Oribatida were more enriched in 13C in European beech than in coniferous forests, but forest type little affected 15 N values of Oribatida across a range of site conditions. We conclude that Oribatida species occupy virtually identical trophic niches (δ13C and δ15N values) irrespective of the soil depth they colonize and that forest management including non‐native tree species little affects trophic position (δ15N values) of oribatid mites. Our findings suggest that the trophic position can be used as a trait in community analysis of Oribatida across forest ecosystems. Our results further indicate that trophic niches of generalist species can be highly consistent irrespective of environment. We studied variations in trophic niches with soil depth and forest types in 40 oribatid mite species using stable isotopes. Trophic positions were remarkable constant irrespective of soil depth and forest type. Therefore, trophic position may be used as quantitative trait in oribatid mite species across different environments.